2018
DOI: 10.5455/medscience.2017.06.8724
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between living arrangements, quality of life and depressive symptoms of older adults

Abstract: This study aimed to investigate the relationship between different types of living arrangement, quality of life and depressive symptoms of older adults. This study was conducted in 2012 in the provincial centre of Kayseri, Turkey. Four groups were formed according to living arrangements of older adults; living alone, living with spouse only, living with spouse and children, living with other family members without spouse. Socio-demographic questionnaire, activities of daily living scale (ADL), World Health Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…With regard to the comparison of the QoL scores with living arrangements in the bivariate analysis, previous findings corroborate the results obtained in the present study, as they indicate that cohabitation with the spouse was positively related to the QoL of older adults (5,7) or because they show that living alone or with their children/others resulted in worse assessments (9,(12)(13)29) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With regard to the comparison of the QoL scores with living arrangements in the bivariate analysis, previous findings corroborate the results obtained in the present study, as they indicate that cohabitation with the spouse was positively related to the QoL of older adults (5,7) or because they show that living alone or with their children/others resulted in worse assessments (9,(12)(13)29) .…”
Section: Discussionsupporting
confidence: 91%
“…Partially ratifying these findings, in a study developed in Turkey, the older adults who lived with other family members and without a spouse also had lower QoL scores in the domains of autonomy and social participation (13) .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…[45] Living with other family members could contribute to a poor economic situation and quality of life, which in turn leads to poorest health, psychosocial distress, and a greater number of chronic illnesses compared to those living with a spouse/partner. [46][47][48] Our study extends the existing literature by providing evidence on the life satisfaction, an important indicator of successful aging, and quality of life. Although living with a spouse offers psychological benefits, many older adults do not live with a spouse either because they have outlived their spouse, or they were never married.…”
Section: Discussionsupporting
confidence: 59%
“…The results showed that psychological wellbeing was better in athlete women compared to non-athlete women. In explaining these finding, we can say that physical activity leads to an improvement in the psychological well-being of individuals by increasing the positive aspects of their personality such as self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth [18][19][20][21][22][23][24]. Actually, physical activity and regular exercise lead to improvement in both mental and physical health status of humans [10,23,25].…”
Section: Discussionmentioning
confidence: 99%